2005
DOI: 10.1128/jvi.79.13.8348-8360.2005
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus ICP27 Activation of Stress Kinases JNK and p38

Abstract: We previously reported that herpes simplex virus type 1 (HSV-1) can activate the stress-activated protein kinases (SAPKs) p38 and JNK. In the present study, we undertook a comprehensive and comparative analysis of the requirements for viral protein synthesis in the activation of JNK and p38. Infection with the UL36 mutant tsB7 or with UV-irradiated virus indicated that both JNK The stress-activated protein kinases (SAPKs) p38 and JNK are part of a larger family of serine/threonine terminal kinases termed mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
76
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 104 publications
5
76
0
Order By: Relevance
“…As expected, HTO-H cells infected with d27-1 virus show little if any JNK phosphorylation (data not shown), consistent with prior results that indicated that ICP27 is required for JNK activation (23,24). In contrast, high levels of nuclear phosphorylated JNK were seen in both KOS and d27-1-infected TE51 cells ( Fig.…”
Section: Icp27-mediated Activation Of Sapkssupporting
confidence: 91%
See 3 more Smart Citations
“…As expected, HTO-H cells infected with d27-1 virus show little if any JNK phosphorylation (data not shown), consistent with prior results that indicated that ICP27 is required for JNK activation (23,24). In contrast, high levels of nuclear phosphorylated JNK were seen in both KOS and d27-1-infected TE51 cells ( Fig.…”
Section: Icp27-mediated Activation Of Sapkssupporting
confidence: 91%
“…The timing of the activation pointed toward an IE gene product as being responsible for initial induction since IE proteins are present at high levels at 3 hpi. Consistent with this, studies showed that ICP27 is required in the context of viral infection for activation of the SAPK pathways (12,23,24). The N-terminal end of the ICP27 protein, which plays a functional role in nuclear export, is required for SAPK activation (12,23,33).…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…Under these circumstances, JNK activation may influence important cellular consequences, such as alterations in gene expression (1,53,59,162,167,176,199,294,325,326,346), cell death (58,89,137,139,169,193,243,293), viral replication, persistent infection or progeny release (215,224,251,260), or altered cellular proliferation (178). The exact mechanism of JNK activation under each of these circumstances remains to be elucidated fully, although there may be involvement of Toll-like receptors, direct pathway modulation through interaction with upstream protein regulators, or the activation following an ER stress response (79,87,110,124,143,191,253,261,279,294,312).…”
Section: Fig 1 Overview Of the Jnk Pathway (A)mentioning
confidence: 99%